Exposure to volatile organic compounds increases the risk of sarcopenia: Insights into association and mechanism - Maosheng Yang; Hanbin Wang; Wenlong Huang; Yi Li (PLoS ONE, 2025)
Background Volatile organic compounds (VOCs) are ubiquitous in our environment, and their associations with sarcopenia are unknown. The aim of this study is to evaluate the association between VOCs exposure and sarcopenia. Methods Data from 2429 U.S. adults (aged ≥ 20 years) were extracted from the NHANES (2011–2018). Logistic regression, LASSO, Weighted Quantile Sum (WQS) and Bayesian Kernel Machine regression (BKMR) analyses were used to assess the associations between VOCs and sarcopenia. Mediation analysis tested roles of inflammation and oxidative stress in this association. The underlying mechanisms were further investigated through database enrichment analysis, molecular docking, and molecular dynamics simulations. Results Among the 2429 adults included, 1213 (49.9%) were male, 1216 (50.1%) were female, and the median age was 39 years (interquartile range, 29–49 years), with a prevalence of sarcopenia of 8.03%. According to the logistic analysis, nine mVOCs were significantly associated with sarcopenia, with N-acetyl-S-(3,4-dihydroxybutyl)-L-cysteine (DHBMA) identified as a potential independent risk factor (odds ratio [OR], 4.51 [95% CI: 1.7–12.1]). WQS analysis revealed a positive association between LASSO-selected 12 mVOCs and sarcopenia (OR 1.39 [95% CI: 1.17–1.90]). BKMR analysis further confirmed this association, with DHBMA showing a significant contribution. Mediation analysis confirmed that inflammation and oxidative stress exert mediating effects. GO and KEGG enrichment analyses indicated that its effects are exerted through the TNF and PI3K–Akt signaling pathways, and that DHBMA binds stably to AKT1. Conclusion This nationally representative cross-sectional study revealed a positive correlation between exposure to mVOCs and sarcopenia via TNF and PI3K–Akt signaling pathways. DHBMA plays a potentially pivotal role in this association.